2017
DOI: 10.1007/s00068-017-0827-1
|View full text |Cite
|
Sign up to set email alerts
|

Deaths caused by injury among people of working age (18–64) are decreasing, while those among older people (64+) are increasing

Abstract: BackgroundInjury is an important cause of death in all age groups worldwide, and contributes to many losses of human and economic resources. Currently, we know a few data about mortality from injury, particularly among the working population. The aim of the present study was to examine death from injury over a period of 14 years (1999–2012) using the Swedish Cause of Death Registry (CDR) and the National Patient Registry, which have complete national coverage.MethodCDR was used to identify injury-related death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 26 publications
3
31
0
Order By: Relevance
“…Contrary to the preclinical assumption of a traumatic cause of the admission, in 25 patients (18.6%), an internal cause (e.g., syncopal fall from a standing position) was the cause of the hospitalization and death. (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) points, p = 0.382). The median (IQR) NISS was 36 (24-57) points.…”
Section: Resultsmentioning
confidence: 98%
“…Contrary to the preclinical assumption of a traumatic cause of the admission, in 25 patients (18.6%), an internal cause (e.g., syncopal fall from a standing position) was the cause of the hospitalization and death. (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) points, p = 0.382). The median (IQR) NISS was 36 (24-57) points.…”
Section: Resultsmentioning
confidence: 98%
“…First (1) is the body regions (head and neck, face, chest, abdomen and pelvis, extremities, external), which come from the sections: head, face, neck, thorax, abdomen and pelvis, spine, upper extremity, lower extremity and external. The second item (2) covers anatomical aspects (whole area, vessels, nerves, organs, skeletal, loss of consciousness), and then specific anatomical structures (3,4) (such as skin abrasion, laceration, amputation, level of consciousness, cervical, lumbar, and so on) followed by the specific injuries (5,6), which are assigned a two-digit number. Last (7) the injuries are then assigned an internal score on a six-grade scale from minor to un-survivable (1 to 6) and a separate "not further specified" score, a score of nine (9).…”
Section: Abbreviated Injury Scale (Ais)mentioning
confidence: 99%
“…Mechanisms of blunt injury in Scandinavia are most common, and of these most happen outside hospital. [3][4][5][6] One of the possible explanations is that in rural areas reporting of incident is delayed, transport times are longer and injuries are more likely to be lethal. 7,8 The most serious mechanisms of injury among patients who survive long enough to get to hospital are three major groups; fall, traffic, and assault.…”
Section: Introductionmentioning
confidence: 99%
“…Intentional self-harm is a major contributor to injury mortality (33,40,70). The decline in intentional self-harm in penetrating injuries could in part be attributed to changing trends in suicide methods as there seems to be a changing trend over time (71,72).…”
Section: Intentionmentioning
confidence: 99%
“…Although there is a difference in the numbers there are some similarities, the most common cause of mortality by handguns is self-inflicted followed by assault in both the United States and Sweden (64). It has been showed that access to firearms contribute to suicides with firearms (70,73). Self-harm injuries with firearms are known to be more lethal than other methods (71).…”
Section: Intentionmentioning
confidence: 99%